2012
DOI: 10.1262/jrd.2012-055
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Ovarian Steroids, Luteinizing Hormone and Estrous Signs from Luteolysis to Ovulation in Lactating and Non-lactating Dairy Cows

Abstract: Abstract. The aims of the present study were to investigate the profiles of ovarian steroids and luteinizing hormone (LH) and the appearance of estrous signs in relation to luteolysis and ovulation in lactating and non-lactating cows and to examine the influence of lactation on those observations. Five lactating (daily milk yield of 28.4 ± 3.2 kg; mean ± SD) and five nonlactating cycling Holstein cows were examined. Their ovaries were monitored by ultrasonography daily during one estrous cycle. Blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, the profiles of E2, P4, and LH in plasma collected at 3-h intervals during the period from natural luteolysis to ovulation did not differ significantly between the lactating and non-lactating dairy cows [27] (Table 1). In this study, the lactating cows were in their mid-lactation period (>80 days postpartum) and had a good nutritional status [27]. It is likely that lactation itself did not disturb the periovulatory endocrine events and that lactating cows could maintain normal estrus cyclicity.…”
Section: Problems With Estrus Detection and Ovulation Disorders In Mo...mentioning
confidence: 94%
See 3 more Smart Citations
“…However, the profiles of E2, P4, and LH in plasma collected at 3-h intervals during the period from natural luteolysis to ovulation did not differ significantly between the lactating and non-lactating dairy cows [27] (Table 1). In this study, the lactating cows were in their mid-lactation period (>80 days postpartum) and had a good nutritional status [27]. It is likely that lactation itself did not disturb the periovulatory endocrine events and that lactating cows could maintain normal estrus cyclicity.…”
Section: Problems With Estrus Detection and Ovulation Disorders In Mo...mentioning
confidence: 94%
“…Previous studies have reported that plasma E 2 concentration around estrus is correlated with the intensity of estrus behavior and duration of estrus [ 25 , 26 ]. To determine the characteristics of ovarian and endocrine profiles during the estrus cycle and periovulatory period in lactating dairy cows, the development of follicles and corpus luteum, plasma concentrations of estradiol-17β (E 2 ), progesterone (P 4 ), and LH, and timing of ovulation were compared with those of non-lactating dairy cows [ 27 , 28 ]. In estrus cycles with two follicular waves, the maximal diameter of the ovulatory follicle is greater in lactating cows than in non-lactating cows [ 28 ].…”
Section: Problems With Estrus Detection and Ovulation Disorders In Mo...mentioning
confidence: 99%
See 2 more Smart Citations
“…LH temporally and rapidly increases just before ovulation in what is called the LH surge. 2 The detection of the LH surge is very important to estimate the optimal artificial insemination period and to improve the conception rate. Measuring estrogen and progesterone levels is useful to estimate the date of calving, 3,4 which helps farmers in achieving safe calving.…”
Section: Introductionmentioning
confidence: 99%